The Implementation of Self Evaluation Teacher Talk (SETT) in Teaching English: A Case Study - Raden Panji Hartono; Slamet Setiawan; Maria Mintowati (Department of English Language Education, UIN Sunan Ampel Surabaya, 2021)
Abstract. This study analyzed the implementation of SETT (Self Evaluation Teacher Talk) (Walsh, 2011) by an English teacher in a senior high school in Surabaya. A descriptive analysis was conducted towards the talk used by teacher in delivering the material. As the law, the teacher regulated the students to speak the target language anyhow. On the other hand, the teacher applied a classroom interaction in English. There are four modes available based on the SETT criteria; managerial mode, material mode, skill and system mode, classroom context mode. The result shown that the teacher mostly applied two mode, namely managerial mode and skill and system mode, and was followed by classroom context mode, then material mode.